What is the figure
please give full question
Answer:
33+12t−21t^2
Step-by-step explanation:
(2t-7)²-(5t-4)²
Use binomial theorem (a−b)^2 = a^2−2ab+b^2 to expand (2t-7)².
4t^2−28t+49−(5t-4)²
Use binomial theorem (a−b)^2 = a^2−2ab+b^2 to expand (5t-4)².
4t^2−28t+49−(25t^2−40t+16)
To find the opposite of 25t^2
−40t+16, find the opposite of each term.
4t^2−28t+49−25t^2−40t+16
Combine 4t^2 and −25t^2 to get −21t^2.
−21t^2−28t+49+40t−16
Combine −28t and 40t to get 12t.
−21t^2+12t+49−16
Subtract 16 from 49 to get 33.
−21t^2+12t+33
Swap terms to the left side.
33+12t−21t^2
I hope this helped!
Answer:
see explanation
Step-by-step explanation:
let ∠BCE = x then ∠ECD = 5x - 6 and
∠BCE + ∠ECD = ∠BCD, substitute values
x + 5x - 6 = 162, that is
6x - 6 = 162 ( add 6 to both sides )
6x = 168 ( divide both sides by 6 )
x = 28
Hence
∠BCE = x = 28°
∠ECD = 5x - 6 = (5 × 28) - 6 = 140 - 6 = 134°